Requirement of Peptidyl-Prolyl Cis/Trans isomerases and chaperones for cellular uptake of bacterial AB-type toxins - Ernst, Katharina (Frontiers in Cellular and Infection Microbiology, 2022)
Bacterial AB-type toxins are proteins released by the producing bacteria and are the causative agents for several severe diseases including cholera, whooping cough, diphtheria or enteric diseases. Their unique AB-type structure enables their uptake into mammalian cells via sophisticated mechanisms exploiting cellular uptake and transport pathways. The binding/translocation B-subunit facilitates binding of the toxin to a specific receptor on the cell surface. This is followed by receptor-mediated endocytosis. Then the enzymatically active A-subunit either escapes from endosomes in a pH-dependent manner or the toxin is further transported through the Golgi to the endoplasmic reticulum from where the A-subunit translocates into the cytosol. In the cytosol, the A-subunits enzymatically modify a specific substrate which leads to cellular reactions resulting in clinical symptoms that can be life-threatening. Both intracellular uptake routes require the A-subunit to unfold to either fit through a pore formed by the B-subunit into the endosomal membrane or to be recognized by the ER-associated degradation pathway. This led to the hypothesis that folding helper enzymes such as chaperones and peptidyl-prolyl cis/trans isomerases are required to assist the translocation of the A-subunit into the cytosol and/or facilitate their refolding into an enzymatically active conformation. This review article gives an overview about the role of heat shock proteins Hsp90 and Hsp70 as well as of peptidyl-prolyl cis/trans isomerases of the cyclophilin and FK506 binding protein families during uptake of bacterial AB-type toxins with a focus on clostridial binary toxins Clostridium botulinum C2 toxin, Clostridium perfringens iota toxin, Clostridioides difficile CDT toxin, as well as diphtheria toxin, pertussis toxin and cholera toxin.